System Dynamics and KPI’s Definition in the Automotive Sector - Nevarez, Omar Villa; Molina, Maria Guadalupe Lopez; Gamino, Juan Alfredo Lino (European Scientific Journal, ESJ, 2017)
In Mexico, the Automotive Industry is one of the most important sectors, based on the amount of sales, as well as for the number of people employed. The level of competition facing firms to win OEM programs requires having a very strict control over the whole company’s operation. System Dynamics is presented as a very powerful methodology for modeling the current and future situation of a company and combined with the Balanced scorecard concept, both provide a deep insight into the dynamics of the company. Based on this case of study a new methodology is proposed which provides a deeper insight on how the system works in such a way that the development of the company’s strategy has greater impact. Through the simulation of 24 months into the future it is possible to understand the system´s behavior in terms of the interrelation of the most critical variables which were defined as the main KPI´s.